2021
DOI: 10.1038/s41598-021-02972-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of favipiravir and remdesivir against human coronavirus NL63 in molecular docking and cell culture models

Abstract: Human coronavirus NL63 (HCoV-NL63) mainly affects young children and immunocompromised patients, causing morbidity and mortality in a subset of patients. Since no specific treatment is available, this study aims to explore the anti-SARS-CoV-2 agents including favipiravir and remdesivir for treating HCoV-NL63 infection. We first successfully modelled the 3D structure of HCoV-NL63 RNA-dependent RNA polymerase (RdRp) based on the experimentally solved SARS-CoV-2 RdRp structure. Molecular docking indicated that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…20 In another study, Wang et al investigated the binding affinities of the favipiravir to SARS-CoV-2 and human coronavirus NL63 RNA-dependent RNA polymerase (RdRp) and indicated that favipiravir has similar binding affinities to these proteins. 22 In the present study, we show for the first time the interactions of these drugs with the ER, PR and HER2 receptors and evaluate their binding affinities. Thus, it will help to understand how ER, PR, and HER2 receptor pathways can be affected in cellular mechanisms in vitro when these drugs are used by normal individuals and breast cancer patients who have COVID-19.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…20 In another study, Wang et al investigated the binding affinities of the favipiravir to SARS-CoV-2 and human coronavirus NL63 RNA-dependent RNA polymerase (RdRp) and indicated that favipiravir has similar binding affinities to these proteins. 22 In the present study, we show for the first time the interactions of these drugs with the ER, PR and HER2 receptors and evaluate their binding affinities. Thus, it will help to understand how ER, PR, and HER2 receptor pathways can be affected in cellular mechanisms in vitro when these drugs are used by normal individuals and breast cancer patients who have COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…Molecular docking studies using either of these drugs in previous studies in the literature have generally investigated the binding of drugs to a SARS-CoV-2 protein. 18,[20][21][22] Celik et al analyzed the interactions of both hydroxychloroquine and chloroquine with proteins of SARS-CoV-2 such as SARS-CoV-2 RNA polymerase, main protease and spike proteins which play an important role in the structure, survival, reproduction, attachment and survival of the SARS-CoV-2 virus. 20 They showed that neither hydroxychloroquine nor chloroquine do not act on SARS-CoV-2 proteins however both molecules prevent the binding of SARS CoV-2 spike protein to angiotensin-converting enzyme 2 (ACE2) by inter-acting with the allosteric site.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro remdesivir shows a broad spectrum of antiviral activity against RNA viruses by targeting replicase such as RdRp [52,72]. Remdesivir can also inhibit the SARS-CoV-2 RdRp [51,53,[73][74][75]. Remdesivir can also dock the 3CLpro replicase [49,51,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…As the experimental validations were found to be partially successful, they have been approved for restricted use only for treating COVID-19 patients belonging to specific groups [32] , [33] , [34] . Similarly, several in silico molecular modelling and preclinical studies have also suggested the plausibility of the above mentioned antiviral compounds to control and prevent the replication and transcription of SARS-CoV-2 [35] . However, those studies have reported different compounds as the top ranked compounds against RdRp [21] , [36] , [37] , [38] .…”
Section: Introductionmentioning
confidence: 93%